Himantoglossum jankae (Orchidaceae: Orchideae), a new name for a long-misnamed lizard orchid - V., Attila Molnár; Kreutz, Karel C. A. J.; Óvári, Miklós; Sennikov, Alexander N.; Bateman, Richard M.; Takács, Attila; Somlyay, Lajos; Sramkó, Gábor (Phytotaxa, 2012)
A new name, Himantoglossum jankae, is given to the widely recognised lizard orchid species that is distributed primarily in the Balkan Peninsula and the northwestern region of Asia Minor and has been erroneously named H. caprinum in most previous literature. The new species differs from its closest relatives in having the combination of relatively large, reddish-purple coloured flowers and labella that bear red papillate spots and comparatively long spurs. We present a morphological description of H. jankae, together with illustrations, distribution information and diagnostic comparisons with H. calcaratum, H. adriaticum and H. caprinum.